AI and Empathy Mapping: Trends and Implication - Homavazir, Zuleika; Dikshit, Sukanya; Gambhir, Vinima; Homavazir, Malcolm (Madhya Bharti Humanities and Social Sciences, 2023)
This research paper explores the intersection of artificial intelligence (AI) and empathy mapping, aiming to understand the current trends and implications of incorporating AI technologies in the process of empathetic understanding and engagement. Empathy mapping, a human-centered design technique, involves gaining insights into users' needs, emotions, and behaviors to create more empathetic and user-centric experiences. With the advent of AI, there is an increasing interest in leveraging AI to enhance empathy mapping practices. This paper reviews the literature on AI and empathy mapping, examines the current trends in this area, and discusses the potential benefits and challenges associated with integrating AI into empathy mapping processes. By understanding the advancements and emerging trends, this research aims to provide insights into the role of AI in fostering empathy and improving user experiences.
ISME
Keywords: Artificial intelligence; AI; empathy mapping; user experience; human-centered design; trends